2021
DOI: 10.1155/2021/2931580
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Probiotics via Autophagy: A Systematic Review

Abstract: Probiotics are living microorganisms increasingly used to treat or modulate different diseases or disorders because of their benefits and also low adverse reaction, and their positive and protective effects on various cells and tissues have been reported. The mechanisms by which probiotics exert their beneficial effects in different cells and tissues were investigated, and autophagy is one of the main mechanisms to induce their positive effects. Autophagy is a conserved process that occurs in all eukaryotic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…However, the fact that SCD Probiotics are more effective here also draws attention because it is reported that the activation of autophagy mechanisms requires a fasting state for a certain period 25 . However, it is known that probiotic bacteria such as Lactobacillus plantarum , which is also included in SCD Probiotics, have the properties of activating the autophagy mechanisms 26 . On the other hand, fully comprehending the differences in the Amid I and Amid II bands used to calculate protein content requires approaches such as proteomics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fact that SCD Probiotics are more effective here also draws attention because it is reported that the activation of autophagy mechanisms requires a fasting state for a certain period 25 . However, it is known that probiotic bacteria such as Lactobacillus plantarum , which is also included in SCD Probiotics, have the properties of activating the autophagy mechanisms 26 . On the other hand, fully comprehending the differences in the Amid I and Amid II bands used to calculate protein content requires approaches such as proteomics.…”
Section: Discussionmentioning
confidence: 99%
“… 25 However, it is known that probiotic bacteria such as Lactobacillus plantarum , which is also included in SCD Probiotics, have the properties of activating the autophagy mechanisms. 26 On the other hand, fully comprehending the differences in the Amid I and Amid II bands used to calculate protein content requires approaches such as proteomics.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms remove misfolded or aggregated proteins and clear damaged organelles like mitochondria, endoplasmic reticulum, and peroxisomes, promoting cell regeneration in the intestinal epithelium. 4 , 35 These findings suggest a broader, more encompassing role for IF and SCD Probiotics in age‐related intestinal health management.…”
Section: Discussionmentioning
confidence: 93%
“…The exact cellular mechanisms related to the beneficial effects of probiotics are not well known. Several investigations, however, have shown that these mechanisms might be associated with stress responses, including several members of heat shock proteins (HSPs), and/or increased efficiency of antioxidant and autophagy cellular mechanisms, resulting in higher cell viability [ 15 ]. It is well known that HSPs are involved in several physiological processes including growth, lifespan, and reproduction stress tolerance [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%